A longitudinal study of maternal endothelial function, inflammatory response and uterine artery blood flow during the second half of pregnancy. (17th November 2015) - Flo, Kari; Blix, Egil S.; Husebekk, Anne; Thommessen, Anders; Uhre, Andreas T.; Wilsgaard, Tom; Vårtun, Åse; Acharya, Ganesh
Abstract: Introduction: The objective of this study was to investigate serial changes in maternal endothelial function, inflammatory response and uterine artery blood flow in normal pregnancy, and to explore their inter‐relation. Material and methods: In this prospective longitudinal observational study, 53 women with uncomplicated pregnancies were examined at 4‐weekly intervals (248 observations) during 22–40 weeks of gestation. Uterine artery blood flow was measured using Doppler ultrasonography. Maternal endothelial function was assessed by flow‐mediated vasodilatation (FMD) of the brachial artery. Circulating endothelial progenitor cells (EPC), defined as CD34 + CD133 + VEGFR2 + cells, were quantified by flow cytometry. Biomarkers of inflammation, such as leptin and high sensitivity C‐reactive protein (hsCRP), were measured in plasma samples. Multilevel modeling was used to investigate gestational‐age‐associated serial changes. Results: The EPC increased from 6.5 to 12.3 per million mononuclear cells ( p < 0.01) and FMD decreased from 16.3 to 13.4% ( p = 0.20). Leptin increased from 18 to 22 ng/mL ( p < 0.01), and hsCRP did not change significantly ( p = 0.61). There was no significant association between FMD and EPC ( p = 0.66). FMD was significantly associated with hsCRP ( p = 0.002) and leptin ( p = 0.003), but the EPC were not. Neither FMD nor EPC were significantly associated with uterine artery blood flow. Conclusion: Changes in FMD were significantly associated with inflammatory biomarkers, suggesting that the reduced nitric oxide‐dependent vasodilatation in late gestation is related to maternal inflammatory response. As EPC and FMD did not correlate, mechanisms other than mobilization of EPC to repair endothelial damage must be responsible for the gestational‐age‐associated increase in EPC.